Excessive use of force by police: a survey of academic emergency physicians. Issue 1 (22nd December 2008) - Hutson, H R; Anglin, D; Rice, P; Kyriacou, D N; Guirguis, M; Strote, J
Abstract : Objective: To determine the clinical experience, management and training of emergency physicians in the suspected use of excessive force by law enforcement officers. Methods: Surveys were mailed to a random sample of academic emergency physicians in the USA. Results: Of 393 emergency physicians surveyed, 315 (80.2%) responded. Of the respondents, 99.8% (95% CI 98.2% to 100.0%) believed excessive use of force actually occurs and 97.8% (95% CI 95.5% to 99.1%) replied that they had managed patients with suspected excessive use of force. These incidents were not reported by 71.2% (95% CI 65.6% to 76.4%) of respondents, 96.5% (95% CI 93.8% to 98.2%) had no departmental policies and 93.7% (95% CI 90.4% to 96.1%) had not received training in the management of these cases. Conclusions: Suspected excessive use of force is encountered by academic emergency physicians in the USA. There is only limited training or policies for the management of these cases.